ANALISIS YURIDIS PERLINDUNGAN KONSUMEN TERHADAP OBAT-OBATAN TRADISIONAL YANG BERASAL DARI LUAR NEGERI BERDASARKAN UNDANG-UNDANG NO. 8 TAHUN 1999 TENTANG KONSUMEN - Efendi, Sumardi; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The State has appointed the Food and Drug Supervisory Agency (BPOM) as a Non Departmental Government Institution established to carry out government duties in the field of drug and food control in accordance with applicable laws and regulations. BBPOM domiciled in Jakarta and to carry out its duties in the area of BBPOM has a technical implementation unit one of them in the form of Center for Food and Drug Supervisor (Balai Besar POM) in the area with their respective working areas. Based on the above background, the authors are interested to explore it more deeply, because with the circulation of these drugs are not accompanied by labels from BPOM, so this can harm consumers as users of these drugs, however health is the main thing, but how it is the case if the sick body is entered by traditional drugs that harm the body, can even result in death.The author sets out the following key issues on How Consumer Protection Against Traditional Drugs Originating From Abroad Based on Law no. 8 of 1999 on Consumers and How Constraints in Consumer Protection Against Traditional Drugs Originating From Abroad Based on Law no. 8 Year 1999 About Consumers.This writing when viewed from the type of research is classified as normative legal research that is research conducted by examining the legal library materials associated with the problem, whereas if viewed from the nature of this research is descriptive research that explains in the form of a clear sentence and detailed.From the results of the research that protection of consumer protection against traditional drugs originating from abroad pursuant to Article 1 paragraph (1) of Law no. 8 Year 1999 About Consumer Protection is any effort that ensures the existence of legal certainty to provide protection to consumers conducted by BBPOM in charge of supervising the circulation of drugs on the market. As an example of a case carried out by BBPOM Pekanbaru who made the arrest of the owner of Drug Store Sumber Rezeki Makmur located in Mal Pekanbaru. From the results of the arrest was confiscated evidence of drugs originating from China bamboo curtain country. Constraints In Consumer Protection Against Traditional Drugs Originating From Abroad Based on Law no. 8 of 1999 About Consumers are: No direct responsibility from pharmaceutical companies to consumers, Lack of supervision conducted by BBPOM on drugs from abroad, lack of human resources, lack of participation from the community and lack of law enforcement to business actors.Keywords: Consumer Protection Traditional Medicine - From Abroad